The adaptive concept of happiness according to Plato’s Gorgias andits current application - Berún-Barrantes, José Antonio (2022)
In the Plato’s Gorgias we can find the answer for two guiding questions inside the ethic platonic approach: the first is an ontological question  how should we live? and the second is an epistemological question how can we know how we should live?; the answers to both questions are related to other concepts such as virtue, goodness, justice and happiness. At the present work we will focus in the concept of happiness according to the Plato’s Gorgias, as one of the paths to answer the questions we are raising and as a way to achieve a peaceful coexistence amongst the men, especially for the times we are living in, where the hedonistic satisfaction of desires may affect other members of the present and future community. While it´s true that the Georgias develops the concepts of rhetoric, justice, goodness and other principles, behind this discussions, we can find this dialog´s other objective which answers the questions sobre la moral that interest us at the present work.